Effect of EDX accelerating voltage on ZnO thin film doped with sodium / Benedict Wen Cheun Au ... [et al.] - Wen, Benedict Cheun Au; Kah, Yoong Chan; Siow, Woon Ng; Fong, Kwong Yam (Universiti Teknologi MARA Cawangan Pahang, 2018)
In recent years, owing to its unique properties, ZnO has been researched extensively for a wide range of applications including sensors, transistors and solar cells. In this work, ZnO thin film doped with sodium (ZnO:Na) was characterized using Field Emission-Scanning Electron Microscopy (FESEM) and Energy Dispersive X-Ray Spectroscopy (EDX). The FESEM image of the ZnO:Na film implies crystal growth at different orientations. The surface composition of the ZnO :Na film with approximately 350 nm thickness was investigated by EDX as a function of accelerating voltage ranging from 5 kV to 15 kV. The EDX spectra revealed that 7 kV is the most appropriate accelerating voltage for extracting elemental composition of the ZnO:Na films, which exclude the detection of the underlying substrate elements. A rectifying structure made up of P-type ZnO :Na film and N-type tin doped indium oxide (ITO) film showed typical rectifying characteristic.